The global economic effects of the COVID-19 pandemic: A bird's-eye view - Begović Boris (Anali Pravnog Fakulteta u Beogradu)
The aim of the article is to provide a general, broad picture of the economic effects of the COVID-19 pandemic, without going into the details. The impact of the pandemic on economic growth was sharp, with sudden and deep decline, followed by complete and swift recovery. Both the supply and the demand side contributed to this dynamic, based on the same factors (morbidity and mortality, behavioural adjustments of individuals, and government pandemic control measures), although with quite distinctive mechanisms of impact. It was the uncertainty of both the supply-and demand-side economic agents that was decisive for the sudden drop in the level of economic activity. Macroeconomic policies, both monetary (quantitative easing) and fiscal (budgetary deficits) proved timely and prevented a global depression. In the aftermath, the side effects of these policies are substantial inflation, increased basic interest rates to counter that inflation, increased sovereign debt, and its threatened sustainability.